Governance analysis for urban-wholesale-to-household’s food waste prevention and reduction in Sri Lanka - Aheeyar, Mohamed M. M.; Jayathilake, Nilanthi; Bucatariu, C.; Reitemeier, M.; Bandara, A.; Thiel, Felix; Drechsel, Pay (CGIAR Research Program on Water, Land and Ecosystems, 2021)
Despite Sri Lanka’s mounting food insecurity and malnutrition affecting over 22% of the population nearly 4,000 tons of food waste (FW) are generated daily, with household and food service sectors contributing the most. Current solid waste streams contain up to 69% food waste, yet national governance frameworks lack direct measures to prevent or reduce it. While policies support broader waste minimization, FW is not clearly recognized as a distinct waste category. Central and provincial policies offer fragmented coverage: Local Authorities are responsible for waste management under several ordinances but lack enforcement capacity. The National Food Act, various environmental and sanitation laws, and the Solid Waste Management Strategy promote composting and safe disposal but omit FW-specific interventions. Only a few policies, such as the Cleaner Production Strategy and Sustainable Consumption and Production Policy, explicitly support FW reduction and circular practices. Key gaps include limited legal enforcement, absence of food safety mandates like HACCP in small food businesses, and a lack of incentive-based mechanisms to drive prevention. Non-state actors such as hotels and charities have adopted voluntary food redistribution and waste reduction measures, but scaling remains limited without systemic support.